Pelatihan Pijat Tui Na Sebagi Strategi dalam Mengatasi Kesulitan Makan Pada Balita di Padukuhan Setan, Kabupaten Sleman - Ratnaningsih, Ester (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Toddlerhood is the golden period of the growth and development process that takes place very rapidly. This period can be realized if the child gets optimal nutritional intake. Efforts to overcome eating difficulties among under-five children can be performed in a non-pharmacological method through tuina massage. This community service aims to observe the effectiveness of tuina massage training to overcome eating difficulties among under-five children in Setan Hamlet, Maguwoharjo Village, Depok Sub-District, Sleman District. Method: Implementation of tuina massage training in mothers with under-five children at for using lecture, discussion and practice methods.. The results community service showed that there was a difference in mother's knowledge before and after the training. The percentage of knowledge before training was in the poorcategory (97%), while the percentage of knowledge after training increased to good category (22%) and moderatecategory (48%). Keywords: TuiNa Massage Training, Mothers with under-five children